Unavoidable Contradictions. A Purpose of the radical Otherness statute of the “colonized females” - Parra, Fabiana (2021)
Maria Lugones in her work leaves us as a legacy the political theoretical project of bringing the anti-racist struggle to the center of the feminist struggle; since, following a logical analysis, a feminism that is not anti-racist, is racist. According to the author, the modern and capitalist colonial gender system, based on hierarchical dichotomies, is characterized by excluding the principle of non-contradiction. In this framework of analysis, the status of colonized females is that of radical alterity. Based on this thesis, Lugones examines the decolonial contributions to the construction of a political theory of Latin American feminisms. In this sense, it arises as an approach to the problem: does upholding the decolonial thesis imply bringing -today- the policy against racism to the center of feminist politics? As a hypothesis, “taking seriously” Lugones’ thesis implies radicalizing the critique of hegemonic Western feminism in its complicity with global racism.